Application of Spectral Kurtosis on vibration signals for the detection of cavitation in centrifugal pumps. (November 2021) - Mousmoulis, G.; Yiakopoulos, C.; Aggidis, G.; Antoniadis, I.; Anagnostopoulos, I.
Abstract: The detection of cavitation formation in hydraulic turbomachinery has been widely investigated due to its significant impact on their steady and dynamic operation. The aim of this study is the application of Spectral Kurtosis tool in order to effectively detect the impulsive shock waves generated during the implosion of vapour bubbles. The methodology is applied and evaluated on the vibration signals obtained from two different semi-open impellers. The results under initial cavitating conditions show that the high frequency implosions of vapour bubbles interact with the low frequency passing of the rotating blades and compose part of the vibration signal. The application of the band pass filter, with central frequency and bandwidth estimated from the Fast Kurtogram, to the original signal allows to extract this information both in time and in frequency domain, and to correlate the periodic impulsive behaviour with the blade passing frequency of the impeller. The present results support the establishment of a robust detection cavitation criterion in centrifugal pumps and show that Spectral Kurtosis is a useful tool for the prevention of related faults in centrifugal pumps.